Association Between Aldehyde dehydrogenase-2 Polymorphisms and Risk of Alzheimer's Disease and Parkinson's Disease: A Meta-Analysis Based on 5,315 Individuals - Chen, Jun; Huang, Wei; Cheng, Chao-Hui; Zhou, Lan; Jiang, Guang-Bin; Hu, Yuan-Yuan (Frontiers in Neurology, 2019)
Objective: A number of studies have reported that aldehyde dehydrogenase-2 (ALDH2) polymorphisms maybe associated with the risk of Alzheimer’s disease (AD) and Parkinson’s disease (PD). However, the results of such studies are inconsistent. We therefore conducted a meta-analysis to clarify the association between ALDH2 polymorphisms and the risk of AD and PD. Methods: Five online databases were searched and the relevant studies were reviewed from inception through May 10, 2018. Odds ratios (ORs) and corresponding 95% confidence intervals (CIs) were calculated in each genetic model of the general population and various subgroups. Furthermore, we simultaneously performed heterogeneity, cumulative, sensitivity, and publication bias analyses. Results: Overall, nine case-control studies involving 5,315 subjects were included in this meta-analysis. Potential associations were found between the ALDH2 rs671 G>A polymorphism and the risk of AD (A vs. G: OR=1.46, 95%CI=1.01-2.11, P=0.05, I2=84.2%; AA vs. GG: OR=2.22, 95%CI=1.03-4.77, P=0.04, I2=79.2%; AA vs. GG+GA: OR=1.94, 95%CI=1.03-3.64, P=0.04, I2=71.1%). In addition, some similar results were observed in other subgroups. Moreover, no significant association between ALDH2 polymorphisms and PD risk. Conclusions: In conclusion, our meta-analysis indicated that the ALDH2 rs671 G>A polymorphism plays an important role in AD development.